Os odontoideum in wolcott-rallison syndrome: a case series of 4 patients. Issue 1 (December 2016) - Dias, R.; Buchanan, C.; Thomas, N.; Lim, S.; Solanki, G.; Connor, SEJ; Barrett, T.; Kapoor, R.
Abstract Wolcott-Rallison Syndrome is the commonest cause of neonatal diabetes in consanguineous families. It is associated with liver dysfunction, epiphyseal dysplasia, and developmental delay. It is caused by mutations in eukaryotic translation initiation factor 2-α kinase 3 (EIF2AK3 ). We report 4 children with WRS and Os Odontoideum resulting in significant neurological compromise. This cervical spine abnormality has not previously been described in this syndrome. This additional evidence broadens the clinical spectrum of this syndrome and confirms the role ofEIF2AK3 in skeletal development. Furthermore, Os Odontoideum needs to be actively screened for in WRS patients to prevent neurological and respiratory compromise.